Sth1, the Key Subunit of the RSC Chromatin Remodeling Complex, Is Essential in Maintaining Chromosomal Integrity and Mediating High Fidelity Chromosome Segregation in the Human Fungal Pathogen Candida albicans - Prasad, Priya; Sanyal, Kaustuv; Ghosh, Santanu K. (Frontiers in Microbiology, 2019)
Chromatin architecture influences gene expression and makes specialized chromatin domains. Factors including histone variants, histone modifiers and chromatin remodelers that define chromatin architecture impact chromosome related processes in Candida albicans. In this context, we sought to investigate the roles of the ATP-dependent chromatin remodeler, Remodel the Structure of Chromatin (RSC) in chromosome segregation of C. albicans. Sth1 is the key ATPase component of RSC and has profound roles in different cellular processes in Saccharomyces cerevisiae. We demonstrate that STH1 is an essential gene in C. albicans. The depletion of Sth1 induces pseudohyphal cells, abnormal spindle morphology, sensitivity towards anti-mitotic drugs and global cohesion defect suggesting an important role of Sth1 in kinetochore-microtubule related processes in C. albicans. Strikingly, Sth1 is required to maintain clustered kinetochores revealing the fact that RSC is required in kinetochore integrity. Taken together, we show that RSC plays an important role in various chromatin-templated processes including chromosome segregation in C. albicans.